2011
DOI: 10.1007/s00211-011-0437-5
|View full text |Cite
|
Sign up to set email alerts
|

Proper generalized decomposition for nonlinear convex problems in tensor Banach spaces

Abstract: Tensor-based methods are receiving a growing interest in scientific computing for the numerical solution of problems defined in high dimensional tensor product spaces. A family of methods called proper generalized decompositions (PGD) methods have been recently introduced for the a priori construction of tensor approximations of the solution of such problems. In this paper, we give a mathematical analysis of a family of progressive and updated PGDs for a particular class of problems associated with the minimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 41 publications
1
77
0
Order By: Relevance
“…It can be noticed that the size of the reduced basis has a considerable influence on both, the local and the global accuracy, however, the influence of τ is negligible. Note that the convergence of the PGD solution in the ∞-norm is not ensured [31], but the experimental results prove that it converges in this particular case. Figure 8 shows the evolution of the error in the parameter identification with the size of the reduced basis.…”
Section: Sensors Placementmentioning
confidence: 86%
“…It can be noticed that the size of the reduced basis has a considerable influence on both, the local and the global accuracy, however, the influence of τ is negligible. Note that the convergence of the PGD solution in the ∞-norm is not ensured [31], but the experimental results prove that it converges in this particular case. Figure 8 shows the evolution of the error in the parameter identification with the size of the reduced basis.…”
Section: Sensors Placementmentioning
confidence: 86%
“…However, it is observed that the decrease in e is not monotonic, with an increase in the 5 th iteration. Although the actual reason of the increase in e has not been investigated here, it can be attributed to the global nature of the PGD based algorithm [22]. Investigating the details about the convergence of PGD based algorithm is a topic of our future research.…”
Section: B Rate Of Convergencementioning
confidence: 98%
“…From Propositions 1 and 2, it is evident that for the dynamical system in (20), the corresponding LQR objective function is given by (22). It is well known that the gain K is can be written as,…”
Section: Linear Quadratic Regulator Using Proper Generalized Decomentioning
confidence: 99%
“…Concerning the variational approach we refer to the following papers: Espig-Hackbusch-Rohwedder-Schneider [7], Falcó-Nouy [8], Holtz-Rohwedder-Schneider [21], Mohlenkamp [26], Osedelets [27] and others cited in these papers.…”
Section: Variational Approachmentioning
confidence: 99%